Anthropometric Assessment of Nutritional Status of Medical Students (Adolescents) - D. Godia, Dr. Haresh; H Nikam, Dr. Lalit (International Journal of Innovative Research in Medical Science, 2018)
Aims: Anthropometric Assessment of Nutritional Status of Medical Students. Material and Method: The present study is carried out on 100 1st M.B.B.S. students of GSMC and tertiary care hospital (50 males and 50 females) not suffering from any major illness. Weighing scale for weight measurement, A scale to measure height (stadiometer), Calipers to measure skin fold thickness. Conclusion: According to BMI: 72% of females and 78% of males are well nourished; 8% of females and 6% of males are over nourished and 20% of females and 16% of males are under-nourished. Considering the consequences or morbidity and mortality associated with undernourishment; corrective steps in the form of improvement in dietary pattern should be undertaken and for over-nourishment; in addition to rectification of diet, more stress should also be laid on doing physical activity. Broca’s Index does not take build into consideration. It therefore gives high values for weight. On the other hand Metropolitan Life Insurance Tables give more accurate estimate of person’s nutritional status and they should be used as a reliable indicator for nutritional assessment. For Adolescent: BMI- Cutt off points as suggested by WHO should be followed rather than following the adult BMI values as the adult BMI value give a high estimate prevalence of malnutrition